Amantadine hydrochloride treatment in heredodegenerative ataxias: a double blind study. - Botez, M I (1996)
OBJECTIVE: A group of 27 patients with Friedreich's ataxia and another group of 30 patients with olivopontocerebellar atrophies were each randomly divided into two subgroups, one receiving placebo and the other amantadine hydrochloride (AH; 200 mg daily) for three to four months. METHODS: The effect of double blind treatment was evaluated by simple visual and auditory reaction time (RT) and movement time (MT) for both right and left hands. RESULTS: The subgroup with olivopontocerebellar atrophies receiving AH showed significant improvement on seven out of eight variables studied by analysis of covariance. In patients with Friedreich's ataxia, improvement was definitely less. Treatment remained contraindicated for those with cardiomyopathies or drug intolerance. CONCLUSION: The rationale of AH use in heredodegenerative ataxias can be explained by its replacement effect (dopamine release) and by direct involvement of N-methyl-D-aspartate (NMDA) in glutamate mediated neurotoxicity in cerebellar granular cells; memantine, an AH analogue, is a potent blocker of NMDA receptors.